CULTURAL RELATIONS BETWEEN TURKEY AND CENTRAL ASIAN COUNTRIES AND ISSUES OF COOPERATION IN THE FIELD OF EDUCATION (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article discusses cooperation between Central Asian countries and the Republic of Turkey in the field of culture and education. Diplomatic relations of the republics, cultural events, cultural events between universities and Turkey, and innovations and cooperation in the field of education will also be discussed. The article Ushbu Mazkuralso Rrtalks haqida firk yuritilingan.lar tilga olinadi.about o`o‘diplomatic relations oo‘`between vathe Republic of o`o‘Central Asian countries and the ning vaRepublic vai haqida fikrlar, besh respublika vaof Turkey o`o‘in lkthe field of giculture `’and ’`education .